WOMEN AND THE REPRODUCTION OF LITERARY NARRATIVES IN THE CONSTRUCTION OF NATION - Wening Udasmoro (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study attempts to explore the positioning of women in literary narratives, particularly in the construction of the space known as “nation”. In discussions of nation and nationhood, these two concepts are frequently attributed to men. Questions of nationhood are also considered masculine, as nationhood is itself narrowly defined as nationalism or defense of the state. In such discussions, women are always excluded, as they are constructed quite differently from men. The narrative of nation is a complex one, in which men and women are differently constructed. Narratives of women are frequently and continuously reproduced, both by men and by women. If, in a social context, narratives of women are continuously reproduced, what are they like in literary narratives that construct the nation? What type of narration of women is constructed? Why is such a construction forefronted? This study specifically explains how women can be continuously present in literature.Keywords: women, construction, narration, nation, literature WANITA DAN REPRODUKSI NARASI SASTRA DALAM KONSTRUKSI BANGSA AbstrakPenelitian ini mencoba mengeksplorasi posisi perempuan dalam narasi sastra, terutama dalam konstruksi ruang yang dikenal sebagai “bangsa”. Dalam diskusi tentang bangsa dan kebangsaan, kedua konsep ini sering dikaitkan dengan laki-laki. Pertanyaan tentang kebangsaan juga dianggap maskulin, karena kebangsaan itu sendiri secara sempit didefinisikan sebagai nasionalisme atau pertahanan negara. Dalam diskusi semacam itu, perempuan selalu dikecualikan, karena dikonstruksi dengan cara yang berbeda dengan laki-laki. Narasi bangsa adalah hal yang kompleks; di dalamnya pria dan wanita dikonstruksi secara berbeda. Narasi perempuan sering dan terus diproduksi ulang, baik oleh pria maupun wanita. Jika dalam konteks sosial narasi perempuan terus-menerus direproduksi, bagaimana narasi perempuan dalam narasi sastra yang mengkonstruksi bangsa? Jenis narasi perempuan apa yang dikonstruksi? Mengapa konstruksi seperti itu dikedepankan? Penelitian ini secara khusus menjelaskan bagaimana wanita dapat terus hadir dalam sastra.Kata kunci: wanita, konstruksi, bangsa, sastra